2021
DOI: 10.1136/gpsych-2020-100347
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in Nigeria: observations from the content analysis of newspapers

Abstract: BackgroundSuicide is a global public health problem and Nigeria is one of the epicentres of suicide in the world. However, there is a dearth of research exploring the epidemiological aspects of suicide in Nigeria.AimTo examine the demographic information and precipitating events for suicides in Nigeria by analysing the contents of newspaper reports of suicide.MethodsWe searched, collected, and analysed published news reports about suicide from 10 English newspapers in Nigeria. A total of 350 suicide reports we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…Our study confirms the findings of previous studies on suicide media reporting in many ways, including mentioning the method of suicide in the headlines and in the reports, providing details of the method, and mentioning the term 'suicide' in the headlines. It is also similar to other studies regarding the lack of expert opinions, research findings, educative information, and suicide prevention contact information (e.g., Arafat et al, (2019); Arafat et al, 2021;Oyetunji et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…Our study confirms the findings of previous studies on suicide media reporting in many ways, including mentioning the method of suicide in the headlines and in the reports, providing details of the method, and mentioning the term 'suicide' in the headlines. It is also similar to other studies regarding the lack of expert opinions, research findings, educative information, and suicide prevention contact information (e.g., Arafat et al, (2019); Arafat et al, 2021;Oyetunji et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…It has long been recognized that individuals with traumatic experiences among persons are at increased risk of subsequently developing poor outcomes, including substance abuse ( 4 ), cognitive deficits ( 5 ), sexual dysfunction ( 6 ), personality disorders ( 7 ) and dissociative disorders ( 8 ). In recent years, abundant evidence has identified that traumatic events play a causal role in serious mental illnesses, including depression ( 8 ), anxiety disorders ( 9 ) and eating disorders ( 10 ), as well as SCZ ( 11 ), these findings has accumulated revealing that trauma/stressful events in childhood/adolescence have potential etiological relationship between the psychotic disorders ( 12 ), and these child traumatic events as a socio-environmental risk factor promote the psychotic symptoms evolving ( 13 ). A recent review and meta-analysis recommended that childhood traumatic events had relationship with offending behavior in SCZ.…”
Section: Introductionmentioning
confidence: 99%
“…Several works of literature identify a common method of suicide in Nigeria to be hanging or jumping from high places; other means include self-poisoning with pesticides and medications [ 30 , 31 , 32 ]. There is an apparent connection between pharmacists and self-poisoning as their core duties are intrinsically linked to medication supply [ 33 ].…”
Section: Community Pharmacists’ Potential Role In Suicide Preventionmentioning
confidence: 99%